Faeces Thesis - closing the nutrient cycle with an architecture of extroversion - Malmkvist, Otto (My University, 2020)
One task for architects in the 2020s, a decade for climate crisis action, is to find sustainable recycling-systems that reduce the amount of waste and maximize the benefits of given resources. Sound and safe, resilient food production that feeds the growing population of this planet is a challenging task that architects may not solve but may help utilize the tools for the solution. Efforts have been made to source separate household waste, but when it comes to the cycling of plant nutrients from human urine and faeces, very little has happened. Agriculture is depending on synthetic fertilizer, which is not only an unsustainable product but also degenerates the soil’s natural capacity to cycle nutrients and binding carbon. The use of drinking water as a means of transport for human waste is a massive waste of resources and complicates the recycling of plant nutrients. This project aims to explore the societal, mental, and spatial obstacles of a recycling toilet system. It intends to present a functional and socially accepted recycling toilet house. Through a collection of prototype user experience data in a student housing building, informed design strategies may be worked out. Which, in turn, will be put in practice within the design task. This thesis’s primary research question is: -How can a small toilet house be a tool to raise awareness about the N and P nutrient cycles. What has been evident in the project is that alternative toilet systems raise much attention and emotions, enthusiasm, and doubt. The intimate and private nature of the act of going to the toilet cannot be underestimated. Functional technical and user-friendly solutions for recycling toilets exist. There are ongoing projects in Sweden that explore bigscale implementation today. Still, there is little written about the perspective of architecture in the field of recycling urine and faeces, although it is a recognized relevant field. To find long-term sustainable solutions, an unassuming dialogue between users, technicians, and designers are fundamental. That is what this thesis wants to explore.
Keywords: recycling toilet, plant nutrients, compost, nutrition loop, source separation, resource management, ecosan